"Itu Sebuah Skandal": Lexical and Sociocultural Interpretation in Critical Discourse Analysis of Fadli Zon's Tweet - Luke, Joice Yulinda; Widyastuti Surtikanti, Monika; Sumarlam, Sumarlam (Humaniora: Journal of Indonesia Culture and Society, 2021)
There were two objectives of the research. The first was to analyze the word ‘scandal’ from textual analysis (micro-level) and sociocultural analysis (macro-level). To analyze the findings, the research made use of Norman Fairclough’s model as the basis of critical discourse analysis. The research was qualitative, which tended to use inductive as the approach. There were 23 informants who participated in the survey and the FGD. They were selected purposively based on their profession and the workplace areas. The data were the four of Fadli Zon’s tweets containing the word ‘scandal’ and its context, which was available in some online media. Research content based on the textual analysis (microanalysis) shows that the text structure is short and directly conveys Fadli Zon’s criticism or negative assumptions toward any policies of government issues. Besides, the macro analysis indicates Fadli Zon has a dominant power to utter the negative judgments toward the government regarding the position in the government structure as one of the leaders in the Indonesian House of Representative. Substantially, the use of specific terms’ scandal’ overall illustrates the negative opinions and indicating declining trust in the policymakers on certain governmental issues. The use of cynicism, sarcasm, and satire styles colors Fadli Zon’s tweets that are also accompanying the overused of ‘scandal’ word. The analysis based on the dimension of discourse practice (micro-level) indicates that using the word ‘scandal’ in Fadli Zon’s tweets is cynical according to the public opinions. The analysis based on the social-cultural practice dimension (macro-level) indicates that Fadli Zon is one Indonesian politician who is often opposed to the Indonesian government policies.